Analisis Pelayanan Kependudukan dan Pencatatan Sipil Melalui Aplikasi e-Open di Kelurahan Bintarajaya Kota Bekasi - Dedi Irawan; Dwi Agustina; Surizki Febrianto; Desak Gede Roche Dian Novita; Purwantomo Purwantomo (Institut Ilmu Sosial dan Manajemen STIAMI, 2022)
This study aims to analyze the innovation of population and civil registration services through the Bekasi City e-Open application in Kelurahan Bintarajaya Village. The research was conducted using a qualitative descriptive analysis method to describe and explain in detail the existing phenomena using interview techniques as a supporting instrument. In this study, innovation in population and civil registration services through the Bekasi City e-Open application in Kelurahan Bintarajaya was measured by 3 (three) performance indicators, namely: responsiveness, responsibility, and accountability. The results of the study conclude that the innovation of population and civil registration services through the Bekasi City e-Open application in Kelurahan Bintarajaya has been running well although there are still shortcomings and obstacles in its implementation. Obstacles to innovation in population and civil registration services through the Bekasi City e-Open application in Kelurahan Bintarajaya include disruption of the serve network system and data overload, which has an impact on the quality of services that is supposed to be fast.